2010
DOI: 10.1016/j.jbiomech.2010.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between local strains and tissue phenotypes in an experimental model of skeletal healing

Abstract: Defining how mechanical cues regulate tissue differentiation during skeletal healing can benefit treatment of orthopaedic injuries and may also provide insight into the influence of the mechanical environment on skeletal development. Different global (i.e., organ-level) mechanical loads applied to bone fractures or osteotomies are known to result in different healing outcomes. However, the local stimuli that promote formation of different skeletal tissues have yet to be established. Finite element analyses can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 36 publications
1
54
0
Order By: Relevance
“…Using Digital Image Correlation (DIC) (Fig. 3), Morgan et al reported a significant correlation between octahedral shear strain and tissue type differentiation, especially in the early steps of bone healing; however, the lowest correlation was between volumetric strain and tissue differentiation (Morgan et al, 2010). In contrast from Claes et al and Carter et al, Prendergast et al considered the shear components of strain to be more compatible with the experimental data.
Fig.
…”
Section: Mechanical Strain and Pressurementioning
confidence: 99%
“…Using Digital Image Correlation (DIC) (Fig. 3), Morgan et al reported a significant correlation between octahedral shear strain and tissue type differentiation, especially in the early steps of bone healing; however, the lowest correlation was between volumetric strain and tissue differentiation (Morgan et al, 2010). In contrast from Claes et al and Carter et al, Prendergast et al considered the shear components of strain to be more compatible with the experimental data.
Fig.
…”
Section: Mechanical Strain and Pressurementioning
confidence: 99%
“…4648 Results from transgenic lineage tracking have shown that the fracture callus is formed mostly of cells from the periosteum. 49 Other studies showed that periosteal cells specifically respond to bone morphogenetic protein 2 (BMP-2) to promote both chondrogenesis and osteogenesis, whereas cells in the marrow space will form only bone in response to BMP-2.…”
Section: Introductionmentioning
confidence: 99%
“…48 Interestingly, when fractures are not stably fixed, angiogenesis is initially increased. 52–54 Excessive interfragmentary instability, however, will impede cartilage replacement, diminish angiogenesis and prevent bone from bridging the fracture gap.…”
Section: Introductionmentioning
confidence: 99%
“…During intramembranous bone formation, mesenchymal progenitor cells condense and directly differentiate into osteoblasts. This occurs during formation of the lateral aspects of the clavicle and many skull bones, as well as during the repair of fully stabilized fractures (e.g., distraction osteogenesis) [5, 6]. In contrast, during endochondral ossification, mesenchymal progenitor cells first form a cartilaginous anlage that becomes vascularized to recruit osteoblast precursors.…”
Section: Introductionmentioning
confidence: 99%